Worldwide Wound Healing Innovation in Natural and Conventional Methods - Joao Vicente da Fonseca, Cesar (IntechOpen, 2016)
The book Worldwide Wound Healing - Innovation in Natural and Conventional Methods develops a set of themes on the healing and treatment of complex wounds through evidence-based practice with innovations in the use of natural and conventional methods. It is an innovative way that promotes the integration of conventional and natural perspectives in wound healing, with a unique focus on the quality of life of the patient.